Targeted Orexin and Hypothalamic Neuropeptides for Migraine - Lauren C. Strother; Anan Srikiatkhachorn; Weera Supronsinchai (My University, 2018)
The hypothalamus is involved in the regulation of homeostatic mechanisms and migraine-related trigeminal nociception and as such has been hypothesized to play a central role in the migraine syndrome from the earliest stages of the attack. The hypothalamus hosts many key neuropeptide systems that have been postulated to play a role in this pathophysiology. Such neuropeptides include but are not exclusive too orexins, oxytocin, neuropeptide Y, and pituitary adenylate cyclase activating protein, which will be the focus of this review. Each of these peptides has its own unique physiological role and as such many preclinical studies have been conducted targeting these peptide systems with evidence supporting their role in migraine pathophysiology. Preclinical studies have also begun to explore potential therapeutic compounds targeting these systems with some success in all cases. Clinical efficacy of dual orexin receptor antagonists and intranasal oxytocin have been tested; however, both have yet to demonstrate clinical effect. Despite this, there were limitations in these cases and strong arguments can be made for the further development of intranasal oxytocin for migraine prophylaxis. Regarding neuropeptide Y, work has yet to begun in a clinical setting, and clinical trials for pituitary adenylate cyclase activating protein are just beginning to be established with much optimism. Regardless, it is becoming increasingly clear the prominent role that the hypothalamus and its peptide systems have in migraine pathophysiology. Much work is required to better understand this system and the early stages of the attack to develop more targeted and effective therapies aimed at reducing attack susceptibility with the potential to prevent the attack all together.
Keywords: Posterior pituitary; Neuroscience of respiration and sleep